PENGETAHUAN HIPERTENSI DENGAN PERILAKU DIET - IRPAN ALI RAHMAN (JURNAL KESEHATAN : JURNAL ILMU- ILMU KEPERAWATAN, KEBIDANAN, FARMASI DAN ANALIS KESEHATAN, SEKOLAH TINGGI KESEHATAN MUHAMMADIYAH CIAMIS, 2020)
Background: Changes in the pattern of life in society and the number of content of certain food elements in the body lead to degenerative diseases, such as hypertension. In West Java Province, Tasikmalaya City has the potential to experience an increase in the incidence of hypertension, reaching 192 per 1000 household members 19.2%, with hypertension sufferers reached 160 cases. Purpose : Objective: To determine the relationship between knowledge of hypertension sufferers and the behavior of undergoing a hypertensive diet. The Method: Using a descriptive-analytic method with a cross-sectional approach, the population and sample in this study were 160 people with hypertension and 114 people using a simple random sampling technique. The data analysis used was Univariate and Bivariate analysis. The validity test was carried out on 20 people. The Result: The lack of knowledge of hypertension sufferers was 55.3%, and the response to not undergoing hypertension diet behavior was 67.5%. Conclusion: Most people with hypertension at the level of knowledge and behavior on a hypertensive diet do not do a hypertension diet.